Intensity-Modulated Radiotherapy for a Rendu-Osler-Weber Disease Patient with Recurrent Severe Epistaxis: A Case Report - Maximilian Niyazi; Marco-Domenico Caversaccio; Patrick Dubach; Andreas Geretschläger; Andreas Arnold; Claus Belka; Daniel M. Aebersold; Norbert M. Blumstein (Case Reports in Medicine)
We present a case of a Rendu-Osler-Weber disease patient with recurrent life threatening epistaxis demanding multiple blood transfusions despite of repetitive endoscopic laser and electrocoagulations, endovascular embolisation, septodermoplasty, and long-term intranasal dressings. As alternative treatment modalities repeatedly failed and the patient became almost permanently dependent on nasal dressing, we performed a highly conformal intensity-modulated radiotherapy of the nasal cavity; a total dose of 50 Gy in 2 Gy single fractions was applied. The therapy was very well tolerated, no acute toxicities occurred. Two weeks after the last radiation dose had been applied, the nasal dressing could be removed without problems. Endoscopical control revealed an almost avascular white mucosa without any trace of bleeding spots; previously existing hemangiomas and crusts had disappeared. After a 1-year-follow up, the patient had no significant recurrent epistaxis.